Pregunta
upstudy study bank question image url

4.2 Hence calculate the value of \( \tan 75^{\circ} \) without using a calculator.

Ask by Coleman Hills. in South Africa
Feb 02,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( \tan 75^{\circ} = 2 + \sqrt{3} \)

Solución

To calculate \( \tan 75^{\circ} \) without using a calculator, we can use the **angle addition formula** for tangent. Here's a step-by-step method: ### Step 1: Express 75° as the Sum of Two Known Angles Choose angles whose tangent values are known. A convenient choice is: \[ 75^{\circ} = 45^{\circ} + 30^{\circ} \] ### Step 2: Use the Tangent Addition Formula The tangent addition formula is: \[ \tan(A + B) = \frac{\tan A + \tan B}{1 - \tan A \tan B} \] Applying this to \( A = 45^{\circ} \) and \( B = 30^{\circ} \): \[ \tan(75^{\circ}) = \frac{\tan 45^{\circ} + \tan 30^{\circ}}{1 - \tan 45^{\circ} \tan 30^{\circ}} \] ### Step 3: Substitute Known Tangent Values We know that: \[ \tan 45^{\circ} = 1 \quad \text{and} \quad \tan 30^{\circ} = \frac{1}{\sqrt{3}} \] Substituting these values: \[ \tan(75^{\circ}) = \frac{1 + \frac{1}{\sqrt{3}}}{1 - 1 \cdot \frac{1}{\sqrt{3}}} \] ### Step 4: Simplify the Expression Multiply numerator and denominator by \( \sqrt{3} \) to eliminate the radicals: \[ \tan(75^{\circ}) = \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \] ### Step 5: Rationalize the Denominator Multiply the numerator and denominator by the conjugate \( (\sqrt{3} + 1) \): \[ \tan(75^{\circ}) = \frac{(\sqrt{3} + 1)^2}{(\sqrt{3})^2 - (1)^2} = \frac{3 + 2\sqrt{3} + 1}{3 - 1} = \frac{4 + 2\sqrt{3}}{2} \] ### Step 6: Final Simplification Divide numerator and denominator by 2: \[ \tan(75^{\circ}) = 2 + \sqrt{3} \] ### **Conclusion** \[ \tan 75^{\circ} = 2 + \sqrt{3} \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To calculate \( \tan 75^{\circ} \) without a calculator, we can use the angle sum identity for tangent: \[ \tan(a + b) = \frac{\tan a + \tan b}{1 - \tan a \tan b} \] Let's express \( 75^{\circ} \) as \( 45^{\circ} + 30^{\circ} \). Now, we know: - \( \tan 45^{\circ} = 1 \) - \( \tan 30^{\circ} = \frac{1}{\sqrt{3}} \) Substituting these values into the identity, we have: \[ \tan 75^{\circ} = \tan(45^{\circ} + 30^{\circ}) = \frac{\tan 45^{\circ} + \tan 30^{\circ}}{1 - \tan 45^{\circ} \tan 30^{\circ}} = \frac{1 + \frac{1}{\sqrt{3}}}{1 - 1 \cdot \frac{1}{\sqrt{3}}} \] Simplifying the numerator and denominator: Numerator: \[ 1 + \frac{1}{\sqrt{3}} = \frac{\sqrt{3} + 1}{\sqrt{3}} \] Denominator: \[ 1 - \frac{1}{\sqrt{3}} = \frac{\sqrt{3} - 1}{\sqrt{3}} \] Thus, we have: \[ \tan 75^{\circ} = \frac{\frac{\sqrt{3} + 1}{\sqrt{3}}}{\frac{\sqrt{3} - 1}{\sqrt{3}}} = \frac{\sqrt{3} + 1}{\sqrt{3} - 1} \] To simplify further, we can multiply the numerator and denominator by \( \sqrt{3} + 1 \): \[ = \frac{(\sqrt{3} + 1)^2}{(\sqrt{3}-1)(\sqrt{3}+1)} = \frac{3 + 2\sqrt{3} + 1}{3 - 1} = \frac{4 + 2\sqrt{3}}{2} = 2 + \sqrt{3} \] So, the value of \( \tan 75^{\circ} \) is: \[ \tan 75^{\circ} = 2 + \sqrt{3} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad